Strategi Pengembangan Produk Roti Mestro (Roti M) untuk Menyasar Pangsa Pasar Baru - Khansa Islami; Muhizan Tamimi; Agung Winarno (Jurnal Informasi Pengabdian Masyarakat, 2023)
Micro, Small and Medium Enterprises (MSMEs) Roti Kopi Maestro operates in the food production sector located in Malang City. A number of challenges arise in business development efforts and industrial competition. To be able to overcome this, strategic planning is very important so that industrial operations can run effectively and efficiently. This research use desciptive qualitative approach. Data was obtained through interviews with business owners, employees, partners and consumers of Roti Maestro. The results of the analysis show that the market development strategy is the most relevant strategy formulation for surviving and creating new market shares